Determinants and consequences of auditor dyad formation at the top level of audit teams - Downar, Benedikt; Ernstberger, Jürgen; Koch, Christopher (Accounting, Organizations and Society, 2021)
This study investigates the determinants and consequences of forming dyads at the top level of audit teams, i.e., dyads between concurring and lead auditor. We apply the sociological theory of homophily, i.e., the implicit preference for similar others, to hierarchically structured auditor dyads. Our regression analyses reveal that sharing the same gender and the same ethnicity, measured by dialect, increases the likelihood of dyad formation beyond what one would expect based on the characteristics of the pool of available auditors. Further, we observe that forming auditor dyads sharing the same age is avoided, suggesting that the need to establish a legitimate hierarchical relationship through social differentiation represents a boundary condition for homophily. Testing for the consequences of auditor dyad formation using an instrumental variable approach, we find that auditor dyads sharing the same dialect provide lower audit quality. We conclude that homophily matters in auditor dyad formation with potentially adverse consequences for audit quality.